'A grass widow's gendered narrative': Renegotiating identities in Lauretta Ngcobo's The prodigal daughter. Issue 2 (3rd July 2019) - Zungu, Evangeline Bonisiwe
Abstract : Ngcobo's oeuvre is primarily concerned with the role of women in the liberation struggle, an area which was widely underestimated by her male counterparts. She uses life-writings to describe the important role played by women in society, and the suffering they experienced within the borders of South Africa and in exile, their courage and commitment, creativity and solidarity in the face of challenges as they performed the roles that were expected of them. Ngcobo's perspective is informed by her identities as Zulu wife and mother, an educated professional, a political activist and a recorder of histories. She describes the core of women's suffering as the denial of conjugal rights and their inability to support the family due to apartheid legislation, which isolated activists and denied them contact with their families and communities. This article uses narrative identity theory to argue that Ngcobo used narrative strategies to reposition herself as a writer, a matriarch, a wife and a political activist. Through narrative identity theory, this article argues that Ngcobo's use of narrative to renegotiate different identities and the focus on African womanhood, cultural expectations and de-womanisation of 'The prodigal daughter' provides a sense of emancipation and wholeness, and contributes to the literature and knowledge about the impact of political consciousness and African ethics on society as a whole.